The key role of the translation of clinical trial protocols in the university training of medical translators - Bolaños-Medina, Alicia (The Journal of Specialised Translation, 2012)
Clinical trials conducted over the last three centuries have made advances in pharmacological knowledge and medical treatments possible. Although the consequences of an inaccurate translation of clinical trial protocols (CTPs) can be very serious in terms of human lives, credibility and economic revenues, translation is rarely given the attention that it requires. An updated insight into the translation of CTPs is offered with special stress on regulatory constraints, cultural aspects, quality assurance, the implementation of technology, the requirements for specialised biomedical translators and the localisation process itself. Finally, several pedagogical features of its instructional potential are presented, particularly those which make the translation of CTPs most suitable to be included in the University training programs of scientific and technical translators, both as an end in itself and as a key methodological step towards the mastery of the translation of other specialised genres.